The relationship of the prevalence of caries with the immune status of preschool and schoolage children in the city of Makhachkala - T. F. Kosyreva; F. I. Osmanovа (LLC "Endo Press", 2023)
Relevance. The study of the relationship between dental morbidity and immune status is relevant due to the high prevalence of caries and the level of somatic health of children in Makhachkala.Materials and methods. The survey involved 425 children aged 2 to 17 years, long-term residents in Makhachkala. The average value of the CPI index corresponds to 5.5. To determine the relationship between the presence of caries and the immune status of children, 33 patients were selected from the examined to participate in a study to determine immunoglobulins in oral fluid in three age periods (11 children aged 6, 12 and 15 years). Oral fluid intake in patients was carried out 2 hours after meals. Determination of the concentration of immunoglobulins (secretory sIgA, IdA, IgM and IgG) was carried out using a set of reagents for enzyme immunoassay determination of the concentration of secretory immunoglobulins in "Invitro". Statistical analysis of the material was carried out using the IBM SPSS Statistics Standard program.Results. In Makhachkala, an increase in the prevalence of caries with age was revealed in preschoolers (6 years) 78.2 ± 0.3%, in adolescence (12 years) 78.9 ± 0.2%, in children with permanent bite (15 years) reaches 85.2 ± 0.6%. Studies of the immune status showed that immunoglobulins varied individually and by age groups. sIgA immunoglobulin, which allows to control immunity before the disease, decreased by more than 3 times by the period of permanent bite. Immunoglobulin IgA, which plays a protective function in humoral immunity, decreased by more than 70% by the period of permanent bite. IgM immunoglobulin increased by more than 40% in children by the age of 15. Changes also occurred with the content of the enzyme lysozyme, decreasing by the age of 15 years almost 6 times from the norm.Conclusions. The high morbidity rate of the children's population in Makhachkala is associated with anthropogenic impact, poor-quality drinking water, air and indicates the need for early detection of chronic somatic diseases and the organization of preventive and medical-dental care for children from an early age.